Study on the Effectiveness of Internet Advertising Based on Consumer Perspectives in Targeting-Challenged Situations - Hori, Kanae; Fujita, Kaede; Ichikawa, Manabu (The Asian Journal of Technology Management (AJTM), 2025)
Abstract. As internet advertising becomes increasingly prevalent, both consumers and advertisers face new challenges, particularly as the phase-out of third-party cookies has reduced the accuracy of ad targeting. In light of such changes, this study examines the effectiveness of online advertising from the consumer's perspective in targeting-constrained environments. An agent-based simulation model was developed to capture the process from ad exposure to purchase and subsequent sharing. The model incorporates key variables such as interest matching, exposure frequency, and social influence. Simulation results demonstrate that even without precise targeting, ad effectiveness can be improved by aligning content with consumer interests and optimizing exposure frequency. These findings offer practical insights into designing privacy-conscious, user-friendly advertising strategies. Keywords: Agent-based modeling, internet advertising, consumer behavior, advertising effectiveness, repeated exposure